Advances in Screening of Edible Fungi Capable of Secreting Laccase and Degradation of Aflatoxin B1 by Laccase from Edible Fungi - LOU Haiwei, YANG Chuangming, ZHAO Yu, NIU Yongwu, TIAN Shuangqi, ZHAO Renyong (Shipin Kexue, 2023)
A large number of grains are contaminated with aflatoxin B1 (AFB1) every year, which causes great harm to the health of humans and livestock. The biodegradation of AFB1, which has the advantages of strong substrate specificity and mild reaction conditions, has attracted considerable attention. Microorganisms safe for consumption should be used to degrade AFB1 in grains in order to avoid introducing new contaminants. Therefore, edible fungi that can secrete laccase are a good choice to degrade AFB1. Based on the NCBI (National Center for Biotechnology Information) and the Uniprot (Unified Protein Database) databases, edible fungi with laccase gene or amino acid sequences are selected, and the reported edible fungi capable of secreting laccase are summarized in this article. Then, the methods used to screen for edible fungi that can secrete laccase are reviewed. In addition, the structure and physicochemical properties of laccase from edible fungi are outlined, and recent progress in understanding the role of laccase in the growth of edible fungi and applying laccase from edible fungi for the degradation of AFB1. It is expected that this review can provide theoretical support for the safe, efficient, and green degradation of AFB1 by laccase from edible fungi.